Fear of missing out and social networking sites use and abuse: A meta-analysis. (September 2021) - Fioravanti, Giulia; Casale, Silvia; Benucci, Sara Bocci; Prostamo, Alfonso; Falone, Andrea; Ricca, Valdo; Rotella, Francesco
Abstract: A growing body of research has examined the potential effects of the Fear of Missing Out (FoMO) on Social Networking Site (SNS) use and Problematic SNS use (PSNSU). The aim of the current meta-analysis is to summarize findings on the relationship between FoMO levels and (i) SNS use and (ii) PSNSU. Furthermore, we meta-analyzed results on the associations between FoMO and some individual characteristics. The sample included 33 independent samples with a total of 21, 473 participants. The results of the random-effects meta-analysis show a positive correlation between FoMO and SNS use and between FoMO and PSNSU, with effect sizes indicating robust associations. Age, sex, and geographic area of the samples did not moderate the associations. FoMO was positively correlated with depression, anxiety, and neuroticism and negatively correlated with consciousness. These results give robustness to the construct validity of FoMO itself, as this concept was introduced to explain why some people might be especially attracted to social media. Moreover, concerns that others might be having rewarding experiences that one is absent from seem to be a trigger for a compulsive use of social platforms, driven by the need to get in touch with others, or as tool to develop social competence. Highlights: A meta-analysis on the relationship between FoMO levels and SNS use and problematic SNS use (PSNSU) was conducted. The effect sizes indicate robust associations between FoMO and both SNS use and PSNUS. Age, sex, and geographic area did not moderate the associations. FoMO should be employed as a relevant dimension in the evaluation and treatment of PSNUS.